Thousands of Years of Pastoralism Don’t Count: Coprophagous Beetles Prefer Exotic Alpaca Dung to That of Cattle - Antonio Rolando; Daniele Bertolino; Alex Laini; Angela Roggero; Claudia Palestrini (Insects)
Dung beetles mostly feed on mammal dung. Throughout the European Alps, the dung produced by local domestic ungulates attracts many species of dung beetles, giving rise to rich and diversified communities that play an important role in the Alpine agricultural ecosystem. There is, therefore, understandable concern about the introduction of exotic livestock, such as alpacas (Vicugna pacos (Linnaeus, 1758)), into the region. This research studied dung beetle assemblages in an Alpine valley where both cattle and alpacas are raised. We used standardized pitfall traps baited with alpaca or cow dung along altitudinal transects to assess the “attractiveness” of the two resources to dung beetles. Most species entered both trap types. The average number of species per trap did not vary significantly and the nMDS trap ordination largely overlapped, but the total number of individuals and the average number of individuals per trap were higher in traps baited with alpaca dung. This difference was largely due to the preference of the dominant species Euheptaulacus carinatus (Germar, 1824) for alpaca dung-baited traps. Moreover, both the abundance and specific richness changed with altitude, being greatest in alpaca traps during July at intermediate altitudes. IndVal analyses showed that eight out of nine species (all Aphodiinae) showed a preference for alpaca traps. Since the microclimatic conditions (i.e., temperature) of the two trap types were virtually the same, it is reasonable to consider trophic preferences as the source of the observed differences. Finally, we also sampled the beetles present in the alpaca latrines and cow dung pats deposited on pastures, providing confirmation that dung beetles do indeed visit the dung of both species. Our results emphasize the usefulness of polyphagia and the trophic flexibility of dung beetles, providing evidence that the long history of pastoralism in the Alps has not led local species to adapt to the dung of domestic ungulates. The results also suggest that alpaca breeding could be a sustainable activity since, thanks to the work of dung beetles which feed upon and move the dung into their tunnels (as occurs with cattle dung), there is less need for farmers to remove the dung from pastures.